Indocyanine Green Near-Infrared Fluoroangiography Is a Useful Tool in Reducing the Risk of Anastomotic Leakage Following Left Colectomy - Neddermeyer, Miriam; Kanngießer, Veit; Maurer, Elisabeth; Bartsch, Detlef K. (Frontiers in Surgery, 2022)
Purpose To evaluate whether visualization of the colon perfusion with indocyanine green near-infrared fluoroangiography (ICG-NIFA) reduces the rate of anastomotic leakage (AL) after colorectal anastomosis. Methods Patients who underwent elective left colectomy, including all procedures involving the sigmoid colon and the rectum with a colorectal or coloanal anastomosis, were retrospectively analyzed for their demographics, operative details, and the rate of AL. Univariate and multivariate analyses were used to compare patients with and without ICG-NIFA-based evaluation. Results Overall, our study included 132 colorectal resections [70 sigmoid resections and 62 total mesorectal excisions (TMEs)], of which 70 (53%) were performed with and 62 (47%) without ICG-NIFA. Patients' characteristics were similar between both the groups. The majority of the procedures [91 (69%)] were performed by certified colorectal surgeons, while 41 (31%) operations were supervised teaching procedures. In the ICG-NIFA group, bowel perfusion could be visualized by fluorescence (dye) in all 70 cases, and no adverse effects related to the fluorescent dye were observed. Following ICG-NIFA, the transection line was changed in 9 (12.9%) cases. Overall, 10 (7.6%) patients developed AL, 1 (1.4%) in the ICG-NIFA group and 9 (14.5%) in the no-ICG-NIFA group (p = 0.006). The multivariate analysis revealed ICG-NIFA as an independent factor to reduce AL. Conclusion These results suggest that ICG-NIFA might be a valuable tool to reduce the rate of AL in sigmoid and rectal resections in an educational setting.